Systems Methodology for Strategic Decision-making in Complex Healthcare System - Jere Jakulin Tadeja (Medicine, Law & Society, 2017)
Systems methodology as a support for strategic decision-making will be discussed in the paper. A society will be presented as a complex system, which is comprised of many smaller, complex systems as its component parts. The healthcare system is one of them. The support to the strategic decision-making in a healthcare system will be shown through systems thinking and systems modelling. We will develop models of a healthcare system in frame of a systems dynamics; a qualitative causal loop diagram (CLD), which helps us to discuss the challenges categorically and a quantitative model, which is a simulation model. Both models illustrate the discussed methodology.